Sleep loss impairs intestinal stem cell function and gut homeostasis through the modulation of the GABA signalling pathway in Drosophila. - Zhou, J.; He, L.; Liu, M.; Guo, X.; Du, G.; Yan, L.; Zhang, Z.; Zhong, Z.; Chen, H. (Cell proliferation, 2023)
Sleep is essential for maintaining health. Indeed, sleep loss is closely associated with multiple health problems, including gastrointestinal disorders. However, it is not yet clear whether sleep loss affects the function of intestinal stem cells (ISCs). Mechanical sleep deprivation and sss mutant flies were used to generate the sleep loss model. qRT-PCR was used to measure the relative mRNA expression. Gene knock-in flies were used to observe protein localization and expression patterns. Immunofluorescence staining was used to determine the intestinal phenotype. The shift in gut microbiota was observed using 16S rRNA sequencing and analysis. Sleep loss caused by mechanical sleep deprivation and sss mutants disturbs ISC proliferation and intestinal epithelial repair through the brain-gut axis. In addition, disruption of SSS causes gut microbiota dysbiosis in Drosophila. As regards the mechanism, gut microbiota and the GABA signalling pathway both partially played a role in the sss regulation of ISC proliferation and gut function. The research shows that sleep loss disturbed ISC proliferation, gut microbiota, and gut function. Therefore, our results offer a stem cell perspective on brain-gut communication, with details on the effect of the environment on ISCs.